The consumption response to minimum wages: Evidence from Chinese households - Ernest Dautovic; Harald Hau; Yi Huang (Graduate Institute of International and Development Studies, 2017)
This paper evaluates the Chinese minimum wage policy for the period 2002-2009 in terms of its impact on low income household consumption. Using a representative household panel, we find support for the permanent income hypothesis, whereby unanticipated and persistent income increases due to minimum wage policy change are fully spent. The impact is driven by households with at least one child. We infer significant positive welfare effects for low income households based on expenditure increases concentrated in health care and education, whereas a negative employment effect of higher minimum wage cannot be confirmed.
Keywords: E24; J38; C26; 330; minimum wages; labor income; household consumption; permanent income hypothesis